2022
DOI: 10.1128/mbio.02969-21
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regulatory Mechanisms Control the Production of CmrRST, an Atypical Signal Transduction System in Clostridioides difficile

Abstract: Clostridioides difficile is a leading cause of hospital-acquired intestinal infections in the United States. The CmrRST signal transduction system controls numerous physiological traits and processes in C. difficile , including cell and colony morphology, motility, biofilm formation, and virulence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In this case, heterogeneity is controlled by a specific DNA recombination event mediated by RecV (38) and the Rho factor (39). In addition, C. difficile colony morphology is also subjected to phenotypic heterogeneity resulting in changes in bacterial physiology and pathogenesis and this occurs through phase variation of the CmrRST signal transduction system expression (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, heterogeneity is controlled by a specific DNA recombination event mediated by RecV (38) and the Rho factor (39). In addition, C. difficile colony morphology is also subjected to phenotypic heterogeneity resulting in changes in bacterial physiology and pathogenesis and this occurs through phase variation of the CmrRST signal transduction system expression (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Sekulovic et al identified the nucleotide within the inverted repeats where recombination occurs for each switch [10]. Deleting this nucleotide and a nucleotide on each side was recently demonstrated to prevent site-specific recombination and inversion of the flg and cmr switches [16,39]. We used this strategy to create strains with the equivalent 3-nucleotide deletion in the right inverted repeat (RIR) of the pdcB switch, one in which the switch is in the reference genome orientation, and the other with the switch in the inverse orientation (Fig 2C).…”
Section: Pdcb Switch Orientation Modulates Pdcb Expressionmentioning
confidence: 99%
“…FN545816) and are listed in S2 Table . To create the plasmids with pdcB (Cdi2) and pdcC (Cdi3) switch fusions to phoZ, the switch regions were PCR amplified from C. difficile R20291 genomic DNA. The PCR products were cloned into pMC123::phoZ (pRT1343) [16] and transformed into DH5α. Transformants were selected on LB-Cm agar and desired clones were identified by PCR and confirmed by sequencing.…”
Section: Dna Manipulation and Strain Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes encoding the CmrST TCS, are phase variable and consists of two RRs and a single HK. CmrRST regulates a variety of cell functions, including colony morphology and motility (Garrett et al, 2019, 2022). The agrACDB locus, homologous to the agr locus in S. aureus , modulates virulence by increasing production of flagella and TcdA (Ahmed et al, 2020; Choudhary et al, 2018; Martin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%